ANALISIS PERKEMBANGAN PEMBERIAN PRODUK KREDIT CEPAT DAN AMAN (KCA) PADA PT. PEGADAIAN (PERSERO) KANWIL V MANADO - Lamampa, Hurul Ain R.; PELLENG, F.A.O.; Sumampouw, H. J. (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract. The existence Pegadaian (Persero) is increasingly important and strategic insupporting policy implementation of government programs in economics and nationaldevelopment. This happens because a lot of people and SMEs who know exactly wherePawnshops are able to contribute both through its lending, with procedures (carrying thecollateral) is easy. Another thing that can affect the Mortgage Loans in improving serviceprovision Quickly and Safely (KCA) to the community is the provision of financing throughloans faster and safer. The purpose of this study was to determine the analysis of thedevelopment of the provision of credit products quickly and safely (KCA) on PT. Pegadaian(Persero).Pawn is an acquired right person indebted on an item on his behalf, and that gives power tothose who were indebted to take repayment of the item is precedence over those of otherindebted; with the exception of charges for the auctioning of goods and which have been issuedto save him after the goods were pawned.This type of research is qualitative research with quantitative approach forecasts. In the processof data collection using observation author. While the data used in the form of primary data anddata analysis used sekunder.Teknik is a trend analysis.The above results can be summarized in 2014 to 2015 reached rise to 11%. Because Pegadaiana lot of money-expenditures for implementation from here can be explained, the imbalancebetween the loan money disbursed by the pawnshop with the gains of the money outstandingloans to customers. However Pegadaian continue to increase its lending to the public bylowering interest rates.KCA mortgage loans to the public and Pegadaian each year has increased from year to year.Increasing the provision of mortgage loans due to the many customers KCA. And can beexpected in the future a more creative, innovative because of the many people who pawned thegoods, then the employee should be conscientious Pegadaian performed the assessment of thepawned goods.Keywords: Quick Credit danAman (KCA), Development Lending.